Relationship between perceived organizational support and organizational commitment among teachers in private primary schools / Mazida Ismail, Muruga Chinniah and Nani Shuhada Sehat - Ismail, Mazida; Chinniah, Muruga; Sehat, Nani Shuhada (2011)
In this knowledge era, education is the most crucial aspect in our lives. In fact, the government as a policy maker imparts a huge sum of money to give the best education to develop nation. Therefore, the needs for getting and retaining the knowledge sources, teachers have become an issue. Schools management plays a vital role to ensure the country does not dry out from the lack of teachers. The purpose of this study was to examine whether there is a significant relationship between perceived organizational support (POS) and three types of organizational commitment (OC) namely affective commitment (AFFOC), continuance commitment (CONTOC) and normative commitment (NORMOC) among private primary school teachers in the Klang Valley. The questionnaires were distributed to chosen private primary schools in the Klang Valley. Data from 103 teachers were analyzed using Pearson's Correlation in Statistical Package for Social Science (SPSS). All variables are proven reliable after going through reliability tests. The findings suggest that there was a positive relationship between POS and all three OC. This indicates that OC among teachers in private primary school is very much dependent on the level of the POS that they received.